UPAYA MENINGKATKAN LITERASI DAN NUMERASI MATEMATIKA SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS VIII SMP NEGERI 4 KABANJAHE TAHUN PEMBELAJARAN 2023-2024 - Febiyola Br Ginting; Sinta Dameria Simanjuntak; Ribka Kariani Sembiring (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to improve students' mathematical literacy and numeracy using the STAD type cooperative learning model for class VIII students at SMP Negeri 4 Kabanjahe. This research is classroom action research (PTK), the subjects in this research are students in class VIII–A of SMP Negeri 4 Kabanjahe. The results of this research show an increase in students' mathematical literacy and numeracy in class VIII–A students at SMP Negeri 4 Kabanjahe for the 2023/2024 academic year. The research procedure is cyclical. Each cycle consists of 4 stages, namely: planning, implementing actions, observing and reflecting. Data collection techniques through observation, tests and questionnaires. This data collection uses several instruments in the form of teacher observation sheets, student observation sheets, questionnaires regarding student responses. Meanwhile, to determine students' mathematical numeracy literacy abilities, tests are used. The results of the research show that the use of the STAD type cooperative learning model can improve students' mathematical numeracy literacy skills in mathematics subjects with flat shapes. From the initial ability test, 5 students got a passing score or 16%, while 27 students did not complete it or 84% with an average score of 50. In the first cycle, 18 students got a passing score or 56%, while students who did not 14 people completed or 44% with an average score of 67. In the second cycle, 26 students got a complete score or 81%, while 6 students did not complete or 16% with an average score of 90. So there was an increase in initial ability test, cycle I and compared to cycle II and has fulfilled the specified completeness. Furthermore, teacher activity in cycle I obtained an average of 73% and in cycle II it increased to 82% and student activity in cycle I obtained an average of 55% and in cycle II it increased to 81%.